1990
DOI: 10.1677/jme.0.0040213
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin binding to chicken adenohypophysial membranes

Abstract: [125I-Tyr1]-Somatostatin (SRIF)-binding sites were demonstrated on crude plasma membrane preparations from chicken pituitary glands. These binding sites were saturable and of high affinity (dissociation constant less than 1.0 nM) and low capacity (maximal binding capacity less than 200 fmol/mg protein) and were specific for SRIF moieties. The number and affinity of these binding sites in the caudal lobe of the pituitary, in which somatotrophs predominate, were similar to those in the cephalic lobe, in which la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In support of this hypothesis, biochemical studies have shown the presence of SS1-related peptides (including SS1 and S-28) but not SS2 in the chicken hypothalamus (Hasegawa et al, 1984). The existence of somatostatin-immunoreactive fibers has been reported for the median eminence of birds (Mikami, 1986), and it has been demonstrated that, in chicken, SS1 inhibits the secretion of growth hormone (Harvey et al, 1978(Harvey et al, , 1990Perez et al, 1987;Donoghue and Scanes, 1991) and prolactin (Harvey et al, 1978). In human and rat (de Lecea et al, 1996(de Lecea et al, , 1997Fukusumi et al, 1997), as in chicken (this study), only the PSS1 gene is expressed in the hypothalamus.…”
Section: Functional Significancementioning
confidence: 85%
See 1 more Smart Citation
“…In support of this hypothesis, biochemical studies have shown the presence of SS1-related peptides (including SS1 and S-28) but not SS2 in the chicken hypothalamus (Hasegawa et al, 1984). The existence of somatostatin-immunoreactive fibers has been reported for the median eminence of birds (Mikami, 1986), and it has been demonstrated that, in chicken, SS1 inhibits the secretion of growth hormone (Harvey et al, 1978(Harvey et al, , 1990Perez et al, 1987;Donoghue and Scanes, 1991) and prolactin (Harvey et al, 1978). In human and rat (de Lecea et al, 1996(de Lecea et al, , 1997Fukusumi et al, 1997), as in chicken (this study), only the PSS1 gene is expressed in the hypothalamus.…”
Section: Functional Significancementioning
confidence: 85%
“…X60191). Although numerous studies have been conducted to determine the distribution of somatostatincontaining neurons (Blä hser, 1984;Nicolardi et al, 1988;Geris et al, 2000) and the effect of SS1 on pituitary hormone secretion in the chicken (Harvey et al, 1978(Harvey et al, , 1990Perez et al, 1987;Donoghue and Scanes, 1991), the existence of a somatostatin variant has not yet been described for birds. In the present study, we have characterized the cDNA encoding PSS2 and have compared the expression pattern of the PSS1 and PSS2 genes in the domestic fowl Gallus gallus.…”
Section: Indexing Terms: Srif; Cortistatin; Central Nervous System; Bmentioning
confidence: 99%
“…Radioreceptor assay studies indicate that pituitary SRIH receptors are comparable in birds and mammals (Harvey et al 1990, Geris et al 2000, and partial cDNAs for chicken SRIH receptors show a high degree of homology with their mammalian counterparts (Bossis & Porter 2001, Boardman et al 2002. Therefore the synthetic non-peptidyl sstr agonists (Rohrer et al 1998) can be useful to identify the receptor pathway through which SRIH controls pituitary functions in this species, as has been shown recently (Bossis & Porter 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous SRIF, conversely, suppresses in-vivo thyroidal function ) and inhibits basal and stimulated GH secretion (Scanes & Harvey, 1989a). SRIF also inhibits basal and stimulated GH release from avian pituitary glands in vitro (Perez, Malamed & Scanes, 1987), by effects probably mediated by membrane SRIF-binding sites (Harvey, Attardo & Baidwan, 1990).…”
mentioning
confidence: 99%